Plant organ modulates morphological constraints of insect-induced galls: evidence from citizen science data - Kanako Bessho-Uehara; Riki Takara; Kosuke Sano; Kohei Tamura (Scientific Reports)
Abstract Galls are abnormal plant structures formed through interactions between host plants and insects, providing shelter and nutrients for gall-inducing insects. As distinct insect species can generate unique gall morphologies even on the same host plant, galls are often viewed as an extended phenotype of the insect. However, since galls consist of plant-derived cells, it is also hypothesized that plant factors shape their morphology. Previous studies exploring this possibility have been restricted to one or a few plant species, limiting broad evolutionary inference. Here, we used citizen science observations to analyze gall morphological complexity across 26 plant orders. Quantitative comparisons using fractal dimension indices revealed that stem-derived galls display significantly less morphological variation than leaf-derived galls. After accounting for the phylogeny of both insects and plants, our model indicated that the originating plant organ influences morphological complexity of galls. Our findings suggest that while gall-inducing insects orchestrate gall development, the developmental properties and plasticity of the plant organ modulate the final morphological outcomes. This study provides a large-scale, cross-species analysis of gall formation and illustrates the power of citizen science in studying morphological evolution.